Faktor-Faktor yang Mempengaruhi Niat Mengadopsi Pertanian Organik di Kabupaten Lima Puluh Kota - Azani, Novia; Tanjung, Hery Bachrizal; Syarfi, Ira Wahyuni (Jurnal Sosial Ekonomi Pertanian, 2025)
Abstract Organic farming is one approach to achieving sustainable agricultural development and solving environmental problems. This study aims to analyze the factors that influence farmers intentions to adopt organic farming in Lima Puluh Kota Regency. This study uses a quantitative approach with a survey method. The location was selected using purposive sampling with the criteria of farmer group members who have obtained organic certification from the West Sumatra Organic Certification Agency (LSO). The sampling technique was conducted using a census, where the entire population became the research sample, consisting of 60 farmers. The research data was sourced from structured interviews using questionnaires, data from the Central Statistics Agency (BPS), and from previous relevant research. Data analysis was performed using multiple linear regression analysis using SPPS 27 software. The results of the study show that of the three variables studied, there are two variables that influence the intention to adopt organic farming in Lima Puluh Kota Regency, namely attitude (0.670) and behavioral control (0.261), while subjective norms (0.096) do not influence the intention to adopt organic farming. Strategies to increase farmers intention to adopt organic farming should focus on improving positive attitudes and perceptions of behavioral control among farmers through education, training, and technical empowerment rather than relying solely on social influence or pressure from surrounding norms